Predictors of Environmental Performance: Mediating Role of Green Supply Chain Management Practices - Kittisak Jermsittiparsert; Parinya Siriattakul; Nuanluk Sangperm (International Journal of Supply Chain Management, 2019)
Eco-friendly concerns has changed the way businesses are being carried out across the globe. The rising environmental concerns have triggered the need for the businesses to consider the impact of their action of the environment which has led to the emergence of the ‘green supply chain management practices’. In this regard this study was conducted to identify the antecedents and outcomes of the green supply chain management. Study identified green knowledge management capability and internal environment management as antecedents and environmental performance as an outcome. 166 procurement managers working in the electronics industry in Thailand gave responses in the study. The results pointed out that green knowledge management capability internal environment management are positively and considerably related with green supply chain management practices. Further results also highlighted that green supply chain management practices are significantly and positively related with environmental performance. Finally the results proved that the green supply chain management is positive significant mediator between relationships of green knowledge management capability, internal environment management and environmental performance.